A handheld milk conductivity sensing device (Mylee) for measuring secretory activation progress in lactating women: a device validation study - Sharon Haramati; Anastasia Firsow; Daniela Abigail Navarro; Ravid Shechter (BMC Pregnancy and Childbirth)
Abstract Background Human milk electrolytes are known biomarkers of stages of lactation in the first weeks after birth. However, methods for measuring milk electrolytes are available only in laboratory or expert settings. A small handheld milk sensing device (Mylee) capable of determining on-site individual secretory activation progress from sensing the conductivity of a tiny milk specimen was developed. Here we evaluate the validity of a novel milk-sensing device (Mylee) for measuring the progress of milk maturation and secretory activation status. Methods Retrospective data analysis of laboratory records generated using the Mylee device. Device conductivity measurements were assessed for accuracy, reliability and stability in rigorous laboratory tests with standard materials. A set of human milk specimens (n = 167) was used to analyze the agreement between the milk maturation score and laboratory measurements of the secretory activation biomarker milk sodium [Na+]. Results The Mylee device was demonstrated to have excellent reproducibility (CV95%<5%) and accuracy (error < 5%) for conductivity measurements of a small specimen (350 µl), with good device stability and almost perfect inter-device unit reliability (ICC > 0.90). With regression analysis, we revealed excellent agreement between Mylee milk maturation (MM%) output or its raw conductivity signal and laboratory measurements of conductivity and sodium [Na+] in a dataset of milk specimens (n = 167; R2 > 0.9). The Mylee MM% score showed good predictive ability for secretary activation status, as determined by sodium threshold (18 mmol/L) in human milk specimens. Conclusions In this study, we demonstrated the reliability and validity of the Mylee device and its ability to detect on-site milk secretory activation in a manner comparable to that of electrolyte-based methods. The novel MyLee device offers the potential to generate real-time information about the lactation stage, measured by mothers at the commodity of their home.